CONSUMER PROTECTION UNDER LAW NUMBER 8 OF 1999 ON PARTIAL CANCELLATION IN MOTOR VEHICLE SALE AND PURCHASE AGREEMENTS - Maisarah Ulfa (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This study examines consumer protection against the unilateral cancellation of motor vehicle sales and purchase agreements, with a focus on the practice at the Berkah Motor business in Banda Aceh, Indonesia. The research method employed is a sociological juridical approach, utilizing primary data collection through interviews and secondary data from laws, regulations, and related literature. The results of the study indicate that a business actor unilaterally canceled the deal due to late installment payments by the consumer, without providing prior information regarding the provisions, and without returning the down payment. This action violates the principle of good faith and the provisions of Articles 7 and 18 of Law Number 8 of 1999 concerning Consumer Protection, which require business actors to provide clear information and prohibit the inclusion of unilateral exoneration clauses. Hence, I argue that although oral agreements are valid and binding, business actors are still obliged to fulfill consumer rights reasonably. In the event of a dispute, Berkah Motor generally resolves the dispute through deliberation to reach a consensus. Still, its effectiveness depends heavily on the good faith of the business owner. If peaceful efforts fail, consumers can pursue legal action through the Consumer Dispute Resolution Agency (BPSK) or the courts. This study highlights the importance of drafting written agreements and the need to enhance legal education for consumers to prevent losses resulting from the unilateral cancellation of verbal contracts.